Soil Contamination and Infection of School Children by Soil-Transmitted Helminths and Associated Factors at Kola Diba Primary School, Northwest Ethiopia: An Institution-Based Cross-Sectional Study - Aschalew Hussein; Megbaru Alemu; Animen Ayehu (Journal of Tropical Medicine)
Background. Soil-transmitted helminths (STHs) are among the most prevalent parasitic worms infecting humans worldwide. They are still a major public health concern in the developing world, school-age children being the most affected segment of the population. Soil polluted with parasite ova and/or infective larvae is a source of human parasitic infections. There is a substantial shift in the notion of sanitation in many countries, and control of STHs contamination in the environment is becoming an emerging topic of research. However, data are scarce on the extent of soil contamination with STHs in Ethiopia in general and the study area in particular. Objective. This study aimed to determine the prevalence of STHs in soil, and school children and associated factors at Kola Diba primary school, Northwest Ethiopia. Methods. A school-based cross-sectional study was conducted in 2020 at Kola Diba primary school. A systematic random sampling technique was used to select 400 participants. About 150 soil samples were collected. A structured Amharic version questionnaire was used to collect data on sociodemographic variables and the factors associated with STH infection. Two grams of stool specimen was processed using the Kato-Katz technique. Data were entered and analyzed using STATA version 14.1. Binary and multiple logistic regressions were performed, and P<0.05 was considered statistically significant. Result. The overall prevalence of soil-transmitted helminths was 50.0% with Ascaris lumbricoides (26.2%), hookworm species (16.5%), and Trichuris trichiura (3.5%). The overall soil contamination rate was 13.3% with A. lumbricoides (9.3%) and T. trichiura (4.0%). No habit of handwashing after toilet (AOR; 2.2, 95%CI: 1.3–3.6, P value = 0.002), no habit of regular shoe-wearing (AOR; 3.7, 95%CI: 2.1–6.2, P value <0.001), untrimmed fingernail status (AOR; 4.3, 95%CI: 2.6–7.1, P value <0.001), and playing with soil (AOR; 3.5, 95%CI: 2.2–5.7, P value <0.001) were significantly associated with STHs infection. Conclusion. The prevalence of STHs remains high among primary school children, with a considerable soil contamination rate. No habit of handwashing after defecation, untrimmed fingernail status, and no habit of regular shoe-wearing and playing with soil were significantly associated with the STHs infections.